Analisis Penerapan Model UTAUT Terhadap Perilaku Pengguna E-Learning (Studi Kasus : STMIK STIKOM Bali) - I Wayan Gede Narayana (LPPM Universitas Dhyana Pura, 2019)
ABSTRACTThe information technology usage which is getting popular makes lots of user change course to utilize that technology especially web, in which in stmik stikom bali there is a web-based system,called elearning, which is very needed. UTAUT model model is used to know the behaviour in using this system. In this research, it will be restricted on the influence analysis of Performance Expectancy, Effort Expectancy, Social Influence, and Faciliting Condition whereas in this research the subjects are the students as users of the system by using PLS (Partial Least Square) as the data processing. The result of the research is that there are 4 independent variables (Performance Expectancy, Effort Expectancy, Social Expectancy, and Facilitating Condition) which are connected with the dependent variable (Behaviour in Use System), there is only 1 variable which has positive influenceKeywords : E-Learning, UTAUT, PLSABSTRAKPenggunaan teknologi informasi yang semakin popular membuat pengguna semakin banyak beralih pada teknologi tersebut khususnya web, dimana pada STMIK STIKOM Bali terdapat system informasi berbasis web yaitu elearning yang sangat dibutuhkan. Dengan menggunakan model UTAUT (Unified Theory of Acceptance and Use of Technology) untuk mengetahui perilaku dalam menggunakan system informasi. Dalam penelitian ini akan dibatasi untuk analisis pengaruh Performace Expectancy, Effort Expectancy, Social Influence dan Faciliting Condition. Dimana dalam penelitian ini akan dilakukan pada mahasiswa sebagai pengguna sistem dengan menggunakan PLS (Partial Least Square) sebagai pengolahan data. Hasil dari penelitian didapat dimana dari 4 variable bebas (Performace Expectancy, Effort Expentancy, Social Influence dan Faciliting Condition )yang dihubungkan dengan variable terikat (Behavior In Use System )hanya 1 variable yang memiliki pengaruh positif.Kata Kunci : E-Learning, UTAUT, PLS